TIPOLOGI GEOMETRI BANGUNAN MEUNASAH DI KECAMATAN INDRAJAYA KABUPATEN PIDIE, ACEH - Hassan, Soraya Masthura; Fefriandi, Fahmi; Fithri, Cut Azmah; Olivia, Sisca (Jurnal Arsitektur ARCADE, 2021)
Abstract: The function of the meunasah in the social system of the Acehnese people is a place of worship, a center for religious and cultural education and is also a place to discuss social problems that occur in community life in the village. The search for characters is important to find typology of meuansah, so that the relationship between geometric typology and shape has a broad interpretation. The search for shape characters to find typology of meunasah in Indrajaya District, Pidie Regency, Aceh was carried out in 5 stages, (1) determine the location of the meunasah building sample points in 52 villages in Indrajaya District, (2) literature review, (3) collecting data on the object of research by measuring the meunasah building, (4) redrawing the meunasah measurements that have been carried out at the data collection stage using digital applications to produce data, namely the meunasah floor plans and facades in each village and the last stage is (5) analysis of determining the type with a geometric approach with architectural elements of the meunasah building facades, namely doors, columns, windows, walls, roofs, floors and terrace fences. The findings consist of 16 types of meunasah typology with similarity criteria of typology variable forms.Abstrak: Keberadaan bangunan meunasah dalam sistem sosial masyarakat Aceh berfungsi sebagai tempat ibadah, pusat Pendidikan kegamaan dan kebudayaan dan juga merupakan tempat untuk mendiskusikan berbagai permasalahan sosial yang terjadi dalam kehidupan masyarakat di gampong tersebut. Pencarian terhadap karakter menjadi penting untuk menemukan tipologi dari meunasah, sehingga katerkaitan tipologi geometri dengan bentuk memiliki intepretasi yang luas. Pencarian karakter bentuk untuk mememukan tipologi dari meunasah di Kecamatan Indrajaya Kabupaten Pidie, Aceh dilakukan melalui 5 tahap yaitu (1) menentukan lokasi titik sampel bangunan meunasah di 52 gampong di Kecamatan Indrajaya, (2) penguatan referensi, (3) pengumpulan data objek penelitian dengan cara pengukuran bangunan meunasah, (4) menggambar ulang pengukuran meunasah yang telah dilakukan pada tahap pengumpulan data menggunakan aplikasi digital untuk menghasilkan data yaitu gambar denah dan tampak meunasah di setiap gampong dan tahap yang terakhir adalah (5) analisis menentukan tipe dengan pendekatan geometri dengan variabel elemen arsitektural dari fasad bangunan meunasah antara lain pintu, kolom, jendela, dinding, atap, lantai dan pagar teras. Penemuan berupa 16 tipe dari tipologi meunasah dengan kriteria kesamaan dan kemiripan dari bentuk variabel tipologi.Â